2005
DOI: 10.1177/0095244305046486
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Finite Element Modeling of Rubber Curing Process

Abstract: This paper describes the development of a finite element model for the simulation of the rubber curing process in a mold. Thermal conductivity and heat capacity of the rubber are assumed to be dependent on temperature. The cure kinetic behavior of the rubber is also assumed to be described by an empirical model proposed by Kamal and Sourour. The governing equation is solved using the finite element method in a three-dimensional Cartesian coordinate system. The applicability of the model is verified by a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…This leads to non-uniform temperature and SOC distributions [10]. To obtain the surface temperature history in tire curing process, the thermocouple method has been used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to non-uniform temperature and SOC distributions [10]. To obtain the surface temperature history in tire curing process, the thermocouple method has been used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some researchers studied the curing process by finite element method for other rubber products [10][11][12][13][14][15][16][17]. Ghoreishy et al [10,11] studied the rubber curing process by finite element method, an advanced computer simulation technique for optimization of the thick rubber article curing process [15]. Besides, the finite element method was used to predict the vulcanization-reversion [16] and optimize the curing process of EPDM weatherstrips [17].…”
Section: Petrochemical Institutementioning
confidence: 99%
“…A literature survey showed that several studies about the prediction of vulcanization evolution were performed. A great amount of these studies took an interest to rubber vulcanization in the instance of molding process [4][5][6][7][8] but only few works concerned the vulcanization of extruded profile by radiant technologies [2,9,10].…”
Section: Nomenclaturementioning
confidence: 99%
“…With the recent advances in computational fluid dynamics to solve the problems related to rotational fluid mechanics ( ), a large number of studies on the flow and mixing mechanism in the kneading disks of the twin-screw extruders use finite element method (FEM) and finite volume method (FVM) (For example, Alsteens et al,2004;Bravo et al, 2004;Ishikawa et al, 2001;Ghoreishy et al, 2005;Nakayama et al, 2011;Rafei et al, 2009;Sobhani et al, 2010;Yoshinaga et al, 2000;Zhang et al,2009.). In a way, although similar in structure and design to the twin-screw extruder, the tri-screw extruder is different from the twin-screw extruder in the flow and mixing mechanisms.…”
Section: Introductionsmentioning
confidence: 99%